Learning Process for Islamic Religious Education Based on Minimum Service Standards for Education - Abdussyukur, Abdussyukur; Mursyidi, Mursyidi; Nicolas, Djone Georges; Syarfuni, Syarfuni; Muflihah, Siti (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This study aims to determine whether or not the learning process of Islamic religious education at State Madrasah Tsanawiyah (MTsN) 3 East Aceh meets the minimum standard for educational services. This objective was motivated by the fact that the majority of regional madrasa education institutions were used as secondary educational institutions by the community due to the perception that the standard of madrasa education was relatively low compared to that of public schools. Based on this history, a study must demonstrate the integrity of the community's viewpoint. The research approach employed is a form of qualitative descriptive research. Researchers collected data through observations, interviews, and documentation. The analysis findings indicate that the learning process for Islamic religious education at MTsN 3 East Aceh satisfies the minimal service requirements for secondary education. MTsN 3 East Aceh implements education by the provisions of educational standards outlined in Permendikbudristek number 32 of 2022 concerning Minimum Education Service Standards and Regulation of the Minister of Religion of the Republic of Indonesia number 2 of 2008 concerning Graduate Competency Standards and Content Standards for Islamic Religious Education in Madrasas.